Historical Reflections: The Rise, Fall, and Resurrection of Software as a Service. - Campbell-Kelly, Martin (Communications of the ACM, 2009)
In this article the author discusses the use of online software services and remote computing. Software as a service (SaaS) occurs when a customer remotely runs software via the Internet, thus utilizing the programs and computer infrastructure of a service provider. The cloud computing services offered by Salesforce.com are also discussed.